Medial defects of the small pulmonary arteries in fatal pulmonary hypertension in infants with trisomy 13 and trisomy 18. Issue 2 (5th December 2013) - Tahara, Masahiro; Shimozono, Saiko; Nitta, Tetsuya; Yamaki, Shigeo
Abstract Congestive heart failure is a major cause of early death in patients with trisomy 13 or 18 and congenital heart disease (CHD). Pulmonary artery banding for these patients early in life is preferred to protect the lungs from high pulmonary flow rates and improve survival. We performed open lung biopsies in 11 patients with trisomy 13 or 18 accompanied by CHD and severe pulmonary artery hypertension (PAH) between 2009 and 2011. Two (18.2%) of these 11 patients had medial defects of the small pulmonary arteries. One patient with trisomy 13 and an atrial septal defect developed lung hemorrhage and lung edema at the age of 9 months and died at the age of 13 months. The lumens of the small pulmonary arteries of the other patient with trisomy 18 and a ventricular septal defect became occluded due to the intimal proliferation of fibrous tissues at the age of 2 months. This patient died at the age of 27 months. The deaths of both patients were associated with heart‐related factors. Patients with medial defects are vulnerable to intimal proliferation in the small pulmonary arteries. More patients with trisomy 13 or 18 and CHD might have similar pulmonary vascular changes. The small pulmonary arteries of patients with trisomy 13 and 18 should be further analyzed. © 2013 Wiley Periodicals, Inc.